Targets and Backgrounds X: Characterization and Representation 2004
DOI: 10.1117/12.539118
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuity and identifiability: efficient calibration tools for synthetic imagery

Abstract: We argue that visual conspicuity and identifiability are two efficient task-related measures that can be deployed to calibrate synthetic imagery that is intended to be used for human visual search and detection tasks. The conspicuity of a target is operationally defined as the region around the center of the visual field where the target is capable to attract visual attention. Visual conspicuity predicts human visual search performance in realistic and military relevant complex scenario's. Conspicuity can easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Whether synthetic imagery is realistic enough will also depend on the military task that is being investigated. Lab measures (such as conspicuity and identifiability) have been proposed to quickly asses the fidelity of detection and identification [25,26].…”
Section: Real Vs Synthetic Imagerymentioning
confidence: 99%
“…Whether synthetic imagery is realistic enough will also depend on the military task that is being investigated. Lab measures (such as conspicuity and identifiability) have been proposed to quickly asses the fidelity of detection and identification [25,26].…”
Section: Real Vs Synthetic Imagerymentioning
confidence: 99%
“…The resulting conspicuity measures reliably predict human visual search performance in realistic and complex scenarios [8,10] for both static objects [10] and dynamic objects [12], in the lab [10,13,14] and in the field [10,15]. Visual conspicuity can also quantify the saliency of camouflaged objects in visual, near-infrared, and thermal imagery [15,16,17]. Depending on the criterion used, one can assess the object's detection or identification conspicuity.…”
Section: Observer Camouflage Metricsmentioning
confidence: 99%
“…As a result, the measurement results can be used to enhance the visual distinctness of the information on the display [72]. For example, traffic sign placement and design can be improved based on the visual simulation and conspicuity measurement in the lab environment [73]. The author also found that observing distance is inversely proportional to the visual conspicuity.…”
Section: Visual Conspicuitymentioning
confidence: 97%